Preferential impairment of later mating stages and sex-dependent metabolic shifts in Japanese medaka exposed to acute acidification - Chih-Ching Chung; Sian-Tai Liu; Jiun-Lin Horng; Ming-Yi Chou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Altered dynamic functional connectivity of the language network associated with electronegative L5 in patients with mild cognitive impairment - Ping-Song Chou; Sharon Chia-Ju Chen; Mei-Chuan Chou; Chung-Yao Hsu; Meng-Ni Wu; Ching-Kuan Liu; Chiou-Lian Lai (GeroScience, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Finite strain pattern inferred from magnetic fabrics across the southern portion of the Central Range, Taiwan - Ya-Chu Tseng; En-Chao Yeh; Ning-Shan Hui; Yu-Min Chou; Jian-Cheng Lee; Ching-Chou Fu (Tectonophysics, 2026)

Amorphous CO2-philic molecular networks via covalent coupling for high-performance TFC hollow fiber membranes - Meta Mamo Goro; Zelalem Gudeta Abdi; Qing-Yun Chou; Ching-Han Chou; Che-Wei Chang; Tai-Shung Chung (Chemical Engineering Journal, 2026)

Centrifuge modeling of tunnel uplift induced by liquefaction under successive seismic motions - Wen-Yi Hung; Jui-Ching Chou; Duc-Trung Tran; Chi-Tam Do (Soil Dynamics and Earthquake Engineering, 2026)

Activity of microbial dark carbon fixation along the gradient of hydrothermal plume inflow by subtropical shallow-water vents - Pei-Chi Ho; Hsiao-Chun Tseng; Wen-Chen Chou; Gwo-Ching Gong (Estuarine, Coastal and Shelf Science, 2026)

Longitudinal association between dietary quality trajectories and cognitive frailty in older adults: a 12-year study of the TIGER cohort - Ting-I. Lee; Bo-Yu Hsiao; Te-Hsuan Huang; Ling-Wei Chen; Yi-Chun Chou; Meei-Shyuan Lee; Jeng-Min Chiou; Yen-Ching Chen; Jen-Hau Chen (GeroScience, 2026)

A coarse-to-fine machine-learning framework for identifying functional connectivity markers of cognitive impairment in Parkinson’s disease - Chung-Yao Chien; Tsung-Lin Lee; Tien-Yu Lin; Rwei-Ling Yu; Chou-Ching K. Lin (Medical & Biological Engineering & Computing, 2026)

Association of CT-derived muscle quality with multiple geriatric syndromes in older adults: a cross-sectional study - Deng-Chi Yang; Chien-Chou Su; Yu-Hsuan Lai; Yi-Ching Yang; Yi-Shan Tsai (GeroScience, 2026)

Anomalous fluid emissions at the Chung-lun mud pool, southwestern Taiwan: evidence for seismic–pore fluid interactions in a thrust fault system - Ching-Chou Fu; Jens Heinicke; Tsanyao Frank Yang; Vivek Walia (International Journal of Earth Sciences, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Atomic-scale CuOx–Fe3O4₋x/TiO2 heterostructures with defect synergy for highly selective and efficient reverse water–gas shift reaction - Po-Wen Cheng; Fa-Chih Pai; Chien-Yi Liu; Chih-Wei Hu; Ching-Yi Chou; Guo-Wei Lee; Chia-Shing Wu; Chun-Hong Kuo; Kuang-Kuo Wang; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Preparation and integration of NIR-to-visible III-substituted In1-xGaxSe multilayers for high-efficiency solar cells and light-emitting devices - Yu-Hung Peng; Ming-Chueh Tsai; Luthviyah Choirotul Muhimmah; Yin-Chou Huang; Yen-Chang Su; Thalita Maysha Herninda; Ching-Hwa Ho (Chemical Engineering Journal, 2026)

Geochemical signatures of mud and core gases from the Milun Fault Scientific Drilling (MiDAS), Taiwan: Implications for fluid pathways and crustal degassing - Ching-Chou Fu; Kuo-Hang Chen; Kuo-Wei Wu; Pei-Ling Wang; Ai-Ti Chen; Vivek Walia; Kuo-Fong Ma (Chemical Geology, 2026)

Establishment of a cobia (Rachycentron canadum) gill cell line: a valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

The tri-bore Pebax/PDMS/PAN multi-layer composite hollow fiber membranes for CO2 capture - Yung-Ching Chia; Ching-Han Chou; Qing-Yun Chou; Jeng-Jyi Hwang; Hui-Hsin Tseng; Yueh-Han Huang; Tai-Shung Chung (Chemical Engineering Journal, 2025)

Interactions between turnover rate and bioactivity of atractylenolide III in Atractylodes macrocephala rhizome in the theory of crude drugs’ pairs and prescriptions in traditional Chinese and Japanese Kampo medicine - Pei-Ying Chou; Yung-Jia Chiu; Che-Chun Lin; Lih-Geeng Chen; Shih-Yi Hsiung; Toshiaki Makino; Ching-Chiung Wang (Journal of Natural Medicines, 2025)

Changes in Prooxidant and Antioxidant-Related Trace Element Levels During Helicobacter pylori Eradication Therapy - Ching-Chiang Lin; Ming-Kun Ku; Hsueh-Chiao Liu; Hui-Wen Chou; Po-Chih Chen; Deng-Chyang Wu; Yeou-Lih Huang (Biological Trace Element Research, 2025)

Molecular insights into the mechanism between the structural and mechanical properties of glycol chitosan methacrylate hydrogels - Kai-Hsiang Chang; Chia-Hung Wu; Zhen-Jie Gao; Yu-Chia Su; Ken-Tsung Wong; Yi-Cheun Yeh; Jiashing Yu; Chia-Ching Chou (Carbohydrate Polymers, 2025)

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunology, 142: 109,134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa by product as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunol. (2023) 142 109134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Photodegradation of tetracycline using O-gCN/SiC/PVDF thin film photocatalysts irradiated with simulated sunlight - Yung-Dun Dai; You-Lin Chou; Ching Yuan (Process Safety and Environmental Protection, 2025)

Corrigendum to “Investigation of seasonal variations in submarine groundwater discharge using radium isotopes under drought conditions in northwestern coastal Taiwan” [J. Hydrol. 649 (2025) 132450] - Minh-Quan Dang; Feng-Hsin Hsu; Chih-Chieh Su; Shih-Jung Wang; Ching-Chou Fu; In-Tian Lin (Journal of Hydrology, 2025)

Prenatal melatonin reprograms liver injury in male pups caused by maternal exposure to a high-fat diet and microplastics - Yu-Jen Chen; Hong-Ren Yu; Ching-Chou Tsai; Mao-Meng Tiao (Apoptosis, 2025)

Correction: Intermittent Hypoxia Activates N-Methyl-D-Aspartate Receptors to Induce Anxiety Behaviors in a Mouse Model of Sleep-Associated Apnea - Yun Fan; Mei-Chuan Chou; Yen-Chin Liu; Ching-Kuan Liu; Chu-Huang Chen; Shiou-Lan Chen (Molecular Neurobiology, 2025)

Pathological and biochemical effects of polyethylene microplastic exposure in hydrothermal vent crab, Xenograpsus testudinatus - Mark June S. Consigna; Li-Chun Tseng; Chi Chou; Ching-Wen Huang; Yi-Ta Shao; Jiang-Shiou Hwang (Marine Pollution Bulletin, 2025)

Investigation of seasonal variations in submarine groundwater discharge using radium isotopes under drought conditions in northwestern coastal Taiwan - Minh-Quan Dang; Feng-Hsin Hsu; Chih-Chieh Su; Shih-Jung Wang; Ching-Chou Fu; In-Tian Lin (Journal of Hydrology, 2025)

Effect of a tropical cyclone on the pelagic ecosystem of a continental shelf - Chung‐Chi Chen; Chih‐hao Hsieh; Yu‐Hsin Cheng; Wei‐Jen Huang; Wen‐Chen Chou; Fuh‐Kwo Shiah; Gwo‐Ching Gong; Tzong‐Yueh Chen (Limnology and Oceanography, 2024)
This study aimed to comprehend the effects of Typhoon Maria on the pelagic ecosystem in the southern East China Sea. Shipboard measurements were conducted at eight sampling stations before (2–4 d) and after (3–6 d) the typhoon, which enabled the evaluation of the potential impacts of the typhoon on this pelagic ecosystem, with particular focus on carbon dynamics. Following the typhoon's passage, there was a slight drop in sea surface temperature. The response of the variables to the typhoon, however, exhibited variations at different sampling stations. For further analysis, t ‐tests compared variables, while type II regression assessed the linear correlation between two variables. Overall, during the post‐typhoon period, concentrations of nitrate, chlorophyll a , primary production, bacterial biomass and production, plankton community respiration, and abundance of large phytoplankton (> 2 μ m) and the relative abundance of picophytoplankton among larger‐sized picoeukaryotes were higher compared to the pre‐typhoon period. The mean value of fugacity of CO 2 was similar to or slightly lower than pre‐typhoon period. Although the typhoon‐induced vigorous primary production might have absorbed a significant amount of CO 2 , the decrease in fugacity of CO 2 could have been offset by the plankton community respiration. The findings suggest that the typhoon enhanced physical disturbance and increased water column mixing, which, in turn, augmented nutrient availability and promoted plankton growth in the shallow water column. Overall, this study sheds light on the complex interactions between typhoons and marine ecosystems and highlights the importance of further investigating these phenomena to better understand their ecological implications.

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Nutrient sources, phytoplankton blooms, and hypoxia along the Chinese coast in the East China Sea: Insight from summer 2014 - Chung-Chi Chen; Wen-Chen Chou; Chin-Chang Hung; Gwo-Ching Gong (Marine Pollution Bulletin, 2024)

Establishment of a cobia (Rachycentron canadum) gill cell line: A valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2024)

Emergence of OXA-48-producing hypervirulent Klebsiella pneumoniae strains in Taiwan - Yi-Tsung Lin; Chien Chuang; Sheng-Hua Chou; Chih-Han Juan; Tsuey-Ching Yang; Barry N. Kreiswirth; Liang Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei) - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2023)

Preparation of an electrochemical sensor utilizing graphene-like biochar for the detection of tetracycline - Chih-Ming Chou; Yung-Dun Dai; Ching Yuan; Yun-Hwei Shen (Environmental Research, 2023)

Uncovering molecular mechanisms involved in microbial volatile compounds-induced stomatal closure in Arabidopsis thaliana - Tu-Trinh Thi Truong; Chi-Chou Chiu; Jing-Yu Chen; Pei-Yu Su; Tri-Phuong Nguyen; Ngoc-Nam Trinh; Tetsuro Mimura; Ruey-Hua Lee; Ching-Han Chang; Hao-Jen Huang (Plant Molecular Biology, 2023)

Severity of Liver Cirrhosis Evaluated by Digital Subtraction Angiography Using Quantitative Color-Coding Analysis Before Transarterial Embolization - Lung-Hui Giiang; Chang-Hsien Liu; Chih-Yung Yu; Te-Pao Lin; Hsiang-Cheng Chen; Chun-Jung Juan; Yu-Ching Chou (Journal of Medical and Biological Engineering, 2023)

Wild salmon enumeration and monitoring using deep learning empowered detection and tracking - William I. Atlas; Sami Ma; Yi Ching Chou; Katrina Connors; Daniel Scurfield; Brandon Nam; Xiaoqiang Ma; Mark Cleveland; Janvier Doire; Jonathan W. Moore; Ryan Shea; Jiangchuan Liu (Frontiers in Marine Science, 2023)
Pacific salmon have experienced declining abundance and unpredictable returns, yet remain vital to livelihoods, food security, and cultures of coastal communities around the Pacific Rim, creating a need for reliable and timely monitoring to inform sustainable fishery management. Currently, spawning salmon abundance is often monitored with in-river video or sonar cameras. However, reviewing video for estimates of salmon abundance from these programs requires thousands of hours of staff time, and data are typically not available until after the fishing season is completed. Computer vision deep learning can enable rapid and reliable processing of data, with potentially transformative applications in salmon population assessment and fishery management. Working with two First Nations fishery programs in British Columbia, Canada, we developed, trained, and tested deep learning models to perform object detection and multi-object tracking for automated video enumeration of salmon passing two First Nation-run weirs. We gathered and annotated more than 500,000 frames of video data encompassing 12 species, including seven species of anadromous salmonids, and trained models for multi-object tracking and species detection. Our top performing model achieved a mean average precision (mAP) of 67.6%, and species-specific mAP scores > 90% for coho and > 80% for sockeye salmon when trained with a combined dataset of Kitwanga and Bear Rivers’ salmon annotations. We also tested and deployed a prototype for a real-time monitoring system that can perform computer vision deep learning analyses on site. Computer vision models and off-grid monitoring systems show promise for automated counting and species identification. A key future priority will be working with stewardship practitioners and fishery managers to apply salmon computer vision, testing and applying edge-capable computing solutions for in-situ analysis at remote sites, and developing tools for independent user-led computer vision analysis by non-computer scientists. These efforts can advance in-season monitoring and decision making to support adaptive management of sustainable wild salmon fisheries.

Duplicated paralog of sulfide: quinone oxidoreductase contributes to the adaptation to hydrogen sulfide-rich environment in the hydrothermal vent crab, Xenograpsus testudinatus - Chi Chen; Guan-Chung Wu; Yao-Tse Chung; Hau-Wen Li; Pei-Hsuan Chou; Yung-Che Tseng; Chieh-Jhen Chen; Sylvie Dufour; Ching-Fong Chang (Science of The Total Environment, 2023)

Hyperlactatemia is associated with increased risks of long-term mortality and major adverse cardiovascular events in sepsis survivors - Shu-Yu Ou; Yi-Jung Lee; Yu-Mei Chou; Gwo-Ching Sun; Yuan-Yi Chia (Infectious Diseases, 2023)

Effect of support condition on the mechanical behavior of ductile iron pipes buried at shallow depth within the backfill of controlled low strength material - Hsuan-Chih Yang; Che-Yu Chang; Gee-Yu Liu; Pao-Ching Chou (Transportation Geotechnics, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Coupling gas purging with inorganic carbon supply to enhance biohydrogen production with Clostridium thermocellum - Changman Kim; Isaac Wolf; Chang Dou; Lauren Magnusson; Pin-Ching Maness; Katherine J. Chou; Steven Singer; Eric Sundstrom (Chemical Engineering Journal, 2023)

Reoxygenation of the Hypoxia in the East China Sea: A Ventilation Opening for Marine Life - Chung-Chi Chen; Dong S. Ko; Gwo-Ching Gong; Chun-Chi Lien; Wen-Chen Chou; Hung-Jen Lee; Fuh-Kwo Shiah; Yu-Sin Wita Huang (Frontiers in Marine Science, 2022)
Hypoxia and upwelling co-occur in the summer, and well-mixed water typically reaches the subsurface in the East China Sea (ECS), especially off the Changjiang River estuary. The impact of upwelling on hypoxia and, therefore, on the ecosystem in the ECS is not known. This study demonstrates both positive and negative effects of upwelling on hypoxia and its impact on the ecosystem. With upwelling, the spatial extent of hypoxic water increases with a lower pH but waters with high regenerated nutrients and fugacity of CO 2 ( f CO 2 ), which are normally confined to the near-bottom, are found just up to 5–10 m below the surface. This upwelled high nutrient water can enhance phytoplankton growth in this region. On one occasion in August 2014, upwelling reached to the surface and lasted for 3 weeks, with the area of coverage ranging from 326.8 to 24,368.0 km 2 . During this event, the water was mixed thoroughly throughout the water column, with high concentrations of nutrients, chlorophyll a , and slightly undersaturated dissolved oxygen but saturated f CO 2 , alongside a normal pH. This event may have served as an important pathway from the ocean to the atmosphere for the regenerated CO 2 . It also provided a productive and suitable environment for marine life and ventilation to alleviate low-oxygen stress in this hypoxic but upwelling region in the ECS.

A Unique Diel Pattern in Carbonate Chemistry in the Seagrass Meadows of Dongsha Island: The Enhancement of Metabolic Carbonate Dissolution in a Semienclosed Lagoon - Wen-Chen Chou; Lan-Feng Fan; Chang-Chang Yang; Ying-Hsuan Chen; Chin-Chang Hung; Wei-Jen Huang; Yung-Yen Shih; Keryea Soong; Hsiao-Chun Tseng; Gwo-Ching Gong; Hung-Yu Chen; Cheng-Kuan Su (Frontiers in Marine Science, 2021)
In contrast to other seagrass meadows where seawater carbonate chemistry generally shows strong diel variations with higher pH but lower partial pressure of CO 2 ( p CO 2 ) during the daytime and lower pH but higher p CO 2 during nighttime due to the alternation in photosynthesis and respiration, the seagrass meadows of the inner lagoon (IL) on Dongsha Island had a unique diel pattern with extremely high pH and low p CO 2 across a diel cycle. We suggest that this distinct diel pattern in pH and p CO 2 could be associated with the enhancement of total alkalinity (TA) production coupled to carbonate sediment dissolution in a semienclosed lagoon. The confinement of the IL may hamper water exchange and seagrass detritus export to the adjacent open ocean, which may result in higher organic matter loading to the sediments, and longer residence time of the water in the IL, accompanied by microbial respiration (both aerobic and anaerobic) that may reduce carbonate saturation level to drive carbonate dissolution and thus TA elevation, thereby forming such a unique diel pattern in carbonate chemistry. This finding further highlights the importance of considering TA production through metabolic carbonate dissolution when evaluating the potential of coastal blue carbon ecosystems to buffer ocean acidification and to absorb atmospheric CO 2 , in particular in a semienclosed setting.

Identification of Neuronal Polarity by Node-Based Machine Learning - Chen-Zhi Su; Kuan-Ting Chou; Hsuan-Pei Huang; Chiau-Jou Li; Ching-Che Charng; Chung-Chuan Lo; Daw-Wei Wang (Neuroinformatics, 2021)
Identifying the direction of signal flows in neural networks is important for understanding the intricate information dynamics of a living brain. Using a dataset of 213 projection neurons distributed in more than 15 neuropils of a Drosophila brain, we develop a powerful machine learning algorithm: node-based polarity identifier of neurons (NPIN). The proposed model is trained only by information specific to nodes, the branch points on the skeleton, and includes both Soma Features (which contain spatial information from a given node to a soma) and Local Features (which contain morphological information of a given node). After including the spatial correlations between nodal polarities, our NPIN provided extremely high accuracy (>96.0%) for the classification of neuronal polarity, even for complex neurons with more than two dendrite/axon clusters. Finally, we further apply NPIN to classify the neuronal polarity of neurons in other species (Blowfly and Moth), which have much less neuronal data available. Our results demonstrate the potential of NPIN as a powerful tool to identify the neuronal polarity of insects and to map out the signal flows in the brain’s neural networks if more training data become available in the future.

Intermittent Hypoxia Activates N-Methyl-D-Aspartate Receptors to Induce Anxiety Behaviors in a Mouse Model of Sleep-Associated Apnea - Yun Fan; Mei-Chuan Chou; Yen-Chin Liu; Ching-Kuan Liu; Chu-Huang Chen; Shiou-Lan Chen (Molecular Neurobiology, 2021)

Clinical Efficacy of a New Robot-assisted Gait Training System for Acute Stroke Patients - Andy Chien; Fei-Chun Chang; Nai-Hsin Meng; Pei-Yu Yang; Ching Huang; Li-Wei Chou (Journal of Medical and Biological Engineering, 2021)
Purpose Robot-assisted gait rehabilitation has been proposed as a plausible supplementary rehabilitation strategy in stroke rehabilitation in the last decade. However, its exact benefit over traditional rehabilitation remain sparse and unclear. It is therefore the purpose of the current study to comparatively investigate the clinical benefits of the additional robot-assisted training in acute stroke patients compared to standard hospital rehabilitation alone. Methods Ninety acute stroke patients (< 3 month) were recruited. All participants received the standard hospital neurorehabilitation comprises 45–60 min sessions daily for 3 weeks. Sixty patients also received an additional 30 min of robot-assisted gait training with the HIWIN MRG-P100 gait training system after each of the standard neurorehabilitation session. Outcome measures included: 1. Berg Balance Scale (BBS); 2. Brunnstrom Stage; 3. Pittsburgh Sleep Quality Index and 4. Taiwanese Depression Questionnaire (TDQ) which were assessed pre-treatment and then after every five training sessions. Results Both groups demonstrated significant improvement pre- and post-treatment for the BBS (robotic group p = 0.023; control group p = 0.033) but no significant difference (p > 0.1) between the groups were found. However, the robotic training group had more participants demonstrating larger BBS points of improvement as well as greater Brunnstrom stage of improvement, when compared to the control group. No significant within and between group statistical differences (p > 0.3) were found for Pittsburgh Sleep Quality Index and Taiwanese Depression Questionnaire. Conclusion The addition of robotic gait training on top of standard hospital neurorehabilitation for acute stroke patients appear to produce a slightly greater improvement in clinical functional outcomes, which is not transferred to psychological status.

Real-time database for geochemical earthquake precursory research - Arvind Kumar; Vivek Walia; Shih-Jung Lin; Ching-Chou Fu (Natural Hazards, 2020)

Short-Term Variability of Biological Production and CO2 System Around Dongsha Atoll of the Northern South China Sea: Impact of Topography-Flow Interaction - Jen-Hua Tai; Wen-Chen Chou; Chin-Chang Hung; Kuan-Chieh Wu; Ying-Hsuan Chen; Tzong-Yueh Chen; Gwo-Ching Gong; Fuh-Kwo Shiah; Chun Hoe Chow (Frontiers in Marine Science, 2020)

Integrating Patient-Specific Electrocardiogram Signals and Image-Based Computational Fluid Dynamics Method to Analyze Coronary Blood Flow in Patients during Cardiac Arrhythmias - Szu-Hsien Chou; Kuan-Yu Lin; Zhen-Ye Chen; Chun-Jung Juan; Chien-Yi Ho; Tzu-Ching Shih (Journal of Medical and Biological Engineering, 2020)
Purpose The aim of this study was to use the computational fluid dynamics (CFD) method, patient-specific electrocardiogram (ECG) signals, and computed tomography three-dimensional image reconstruction technique to investigate the blood flow in coronary arteries during cardiac arrhythmia. Methods Two patients with premature ventricular contraction-type cardiac arrhythmia and one with atrial fibrillation-type cardiac arrhythmia were investigated. The inlet velocity of the coronary artery in simulation was applied with the measured velocity profile of the left ventricular outflow tract (LVOT) from the Doppler echocardiography. The measured patient central aortic blood pressure waveform was employed for the coronary artery outlet in simulation. The no-slip boundary condition was applied to the arterial wall. Results For the patient with irregular cardiac rhythms (Case I), the coronary blood flow rate under the shortened and lengthened cardiac rhythms were 0.66 and 0.96 mL/s, respectively. In Case II, the maximum velocity at the LVOT under a normal heartbeat was found to be 101 cm/s, whereas the average value was 73 cm/s. In Case III, the patient was also diagnosed with a congenital stenosis problem at the myocardial bridge (MCB) at the LAD. The measured blood flow rate at the MCB of the LAD for the three heartbeats in Case III was found to be 0.68, 1.08, and 1.14 mL/s. Conclusion The integration of patient-specific ECG signals and image-based CFD methods can clearly analyze hemodynamic information for patients during cardiac arrhythmia. The cardiac arrhythmia can reduce the blood flow in the coronary arteries.

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

Comparative Study of Regulations of Devices for Aesthetic Purposes: US, European Union, China, and Taiwan - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2020)

Urinary biomarkers of polycyclic aromatic hydrocarbons and the association with hearing threshold shifts in the United States adults - Cheng-Wai Chou; Yuan-Yuei Chen; Chung-Ching Wang; Tung-Wei Kao; Chen-Jung Wu; Ying-Jen Chen; Yi-Chao Zhou; Wei-Liang Chen (Environmental Science and Pollution Research, 2020)

In vitro activities of imipenem, vancomycin, and rifampicin against clinical Elizabethkingia species producing BlaB and GOB metallo-beta-lactamases - Tein-Yao Chang; Hsing-Yu Chen; Yu-Ching Chou; Yun-Hsiang Cheng; Jun-Ren Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Soil gas survey in and around Shanchiao fault of northern Taiwan for establishing continuous monitoring station - Arvind Kumar; Vivek Walia; Yi-Chun Sung; Shih-Jung Lin; Ching-Chou Fu; Kuo-Liang Wen (Acta Geophysica, 2018)

Effects of normoxic and hypoxic exercise training on the bactericidal capacity and subsequent apoptosis of neutrophils in sedentary men - Yi-Ching Chen; Wan-Yu Chou; Tieh-Cheng Fu; Jong-Shyan Wang (European Journal of Applied Physiology, 2018)

Seasonal variation and source apportionment of PM2.5-bound trace elements at a coastal area in southwestern Taiwan - Su-Lun Hwang; Miao-Ching Chi; Su-Er Guo; Yu-Ching Lin; Chiang-Ting Chou; Chieh-Mo Lin (Environmental Science and Pollution Research, 2018)

Status quo of management of the human tissue banks in Taiwan - Ching-Pang Chou; Szu-Cheng Chou; Ying-Hua Chen; Yu-Hsuan Chen; Ming-Shin Lee (Cell and Tissue Banking, 2017)

The formation and evolution of a coastal alluvial fan in eastern Taiwan caused by rainfall-induced landslides - Hsien-Ter Chou; Ching-Fang Lee; Chia-Ming Lo (Landslides, 2017)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

Insulin Receptor Substrate-1 Activation Mediated p53 Downregulation Protects Against Hypoxic-Ischemia in the Neonatal Brain - Yi-Fang Tu; Si-Tse Jiang; Yen-Hung Chow; Chao-Ching Huang; Chien-Jung Ho; Ya-Ping Chou (Molecular Neurobiology, 2016)

Relationships between urban open spaces and humans’ health benefits from an ecological perspective: a study in an urban campus - Wan-Yu Chou; Ching-Hsien Lee; Chun-Yen Chang (Landscape and Ecological Engineering, 2016)

Using Free Navigation Reference Points and Prefabricated Bone Plates for Zygoma Fracture Model Surgeries - Tien-Hsiang Wang; Hsu Ma; Ching-Shiow Tseng; Yi-Hong Chou; Kun-Lin Cai (Journal of Medical and Biological Engineering, 2016)

MicroRNA let-7g cooperates with interferon/ribavirin to repress hepatitis C virus replication - Wen-Wen Chou; Chung-Feng Huang; Ming-Lun Yeh; Yi-Shan Tsai; Ming-Yen Hsieh; Ching-I Huang; Jee-Fu Huang; Pei-Chien Tsai; Edward Hsi; Suh-Hang Hank Juo; Wei-Lun Tsai; Wan-Long Chuang; et al. (Journal of Molecular Medicine, 2016)

Identifications and removal of diurnal and semidiurnal variations in radon time series data of Hsinhua monitoring station in SW Taiwan using singular spectrum analysis - Arvind Kumar; Vivek Walia; Baldev Raj Arora; Tsanyao Frank Yang; Shih-Jung Lin; Ching-Chou Fu; Cheng-Hong Chen; Kuo-Liang Wen (Natural Hazards, 2015)

Medical Image Enhancement Using Modified Color Histogram Equalization - Wei-Yen Hsu; Ching-Yao Chou (Journal of Medical and Biological Engineering, 2015)

Robot-Assisted Passive Exercise for Ankle Hypertonia in Individuals with Chronic Spinal Cord Injury - Chia-Ying Fang; Miao-Ju Hsu; Chih-Chung Chen; Hsin-Yi Kathy Cheng; Ching-Chieh Chou; Ya-Ju Chang (Journal of Medical and Biological Engineering, 2015)

Who wants a free brain scan? Assessing and correcting for recruitment biases in a population-based sMRI pilot study - Mary Ganguli; Ching-Wen Lee; Tiffany Hughes; Beth E. Snitz; Jennifer Jakubcak; Ranjan Duara; Chung-Chou H. Chang (Brain Imaging and Behavior, 2015)

Aerosolized bovine lactoferrin reduces lung injury and fibrosis in mice exposed to hyperoxia - Hsiao-Ling Chen; Chih-Ching Yen; Shih-Ming Wang; Tung-Chou Tsai; Zi-Lun Lai; Jheng-Yue Sun; Willei Lin; Wu-Huei Hsu; Chuan-Mu Chen (BioMetals, 2014)

Divergence of the expression and subcellular localization of CCR4-associated factor 1 (CAF1) deadenylase proteins in Oryza sativa - Wei-Lun Chou; Li-Fen Huang; Jhen-Cheng Fang; Ching-Hui Yeh; Chwan-Yang Hong; Shaw-Jye Wu; Chung-An Lu (Plant Molecular Biology, 2014)

Development of a loop-mediated isothermal amplification method for rapid detection of pigeon circovirus - Shinn Shyong Tsai; Yeng Ling Chang; Yen Li Huang; Hung Jen Liu; Guan Ming Ke; Chwei Jang Chiou; Yao Ching Hsieh; Tsung Chou Chang; Li Ting Cheng; Kuo Pin Chuang (Archives of Virology, 2014)

Landslide at Su-Hua Highway 115.9k triggered by Typhoon Megi in Taiwan - Chia-Ming Lo; Ching-Fang Lee; Hsien-Ter Chou; Ming-Lang Lin (Landslides, 2014)

Diverse chromosome complements in the functional gametes of interspecific hybrids of MT- and A-karyotype Lycoris spp. - Yu-Chu Chang; Chou-Tou Shii; Yi-Ching Lee; Mei-Chu Chung (Plant Systematics and Evolution, 2013)

A study of the frequency of methylation of gene promoter regions in colorectal cancer in the Taiwanese population - CHANG-CHIEH WU; JEN-CHUN KUAN; CHIH-HSIUNG HSU; TZU-AN CHEN; CHIEN-AN SUN; TSAN YANG; SHINN-LONG LIN; YU-CHING CHOU (Journal of Genetics, 2013)

Lipopolysaccharide/adenosine triphosphate-mediated signal transduction in the regulation of NLRP3 protein expression and caspase-1-mediated interleukin-1β secretion - Pei-Chun Liao; Louis Kuoping Chao; Ju-Ching Chou; Wei-Chih Dong; Chien-Nan Lin; Chai-Yi Lin; Ann Chen; Shuk-Man Ka; Chen-Lung Ho; Kuo-Feng Hua (Inflammation Research, 2013)

Associations Between Water Quality Parameters and Planktonic Communities in Three Constructed Wetlands, Taipei - Pen-Yuan Chen; Pei-Fen Lee; Chie-Jen Ko; Chun-Han Ko; Ta-Ching Chou; Chia-Ji Teng (Wetlands, 2011)

Characterization of Expressed Sequence Tags from Flower Buds of Alpine Lilium formosanum using a Subtractive cDNA Library - Wei-Kuang Wang; Chia-Chin Liu; Tzen-Yuh Chiang; Ming-Tse Chen; Chang-Hung Chou; Ching-Hui Yeh (Plant Molecular Biology Reporter, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Trace metal cycling in the surface water of the South China Sea: Vertical fluxes, composition, and sources - Tung-Yuan Ho; Wen-Chen Chou; Ching-Ling Wei; Fei-Jan Lin; George T. F. Wong; Hui-Ling Line (Limnology and Oceanography, 2010)
We deployed floating traps in the surface waters of the South China Sea on four occasions at depths of 30 m, 100 m, and 160 m from 2006 to 2007 to quantify vertical metal fluxes in the surface water and examine trace metal composition in the sinking particles to investigate their sources. The elements determined include 13 trace metals and 8 major elements. The fluxes for most of the bioactive elements at 30 m varied markedly during different seasons and strongly co‐varied with organic matter production, but the fluxes at 160 m were low and consistent under different seasons, showing that most of the elements were internally recycled in the surface water during productive seasons. Most of the bioactive trace metals in sinking particles were correlated with biogenic P, and their P‐normalized quotas were also strongly associated with lithogenic Al. The ratios of metals to Al and P for most of the bioactive trace metals were significantly higher than the ratios in lithogenic particles and than intracellular quotas in plankton, respectively, indicating that the trace metals in the sinking particles were abiogenic, nonlithogenic, and adsorbed on biogenic particles. The comparable fluxes between aeolian deposition and the sinking particles in the mixed layer demonstrate that the highly enriched trace metals in the sinking particles were attributed to input from anthropogenic aerosols. The coupling and transport of anthropogenic trace metals with biogenic particles in oceanic surface waters may be an important mechanism for trace metal cycling in global oceans.

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Proteomic Analysis of the Effect of Cyanide on Klebsiella oxytoca - Petrus Tang; You-Cheng Hseu; Hui-Hsuan Chou; Kuo-Yang Huang; Ssu Ching. Chen (Current Microbiology, 2010)

Model analyses of visual biofeedback training for EEG-based brain-computer interface - Chih-Wei Chen; Ming-Shaung Ju; Yun-Nien Sun; Chou-Ching K. Lin (Journal of Computational Neuroscience, 2009)

Production of cyclodextrin glucanotransferase from an alkalophilic Bacillus sp. by pH-stat fed-batch fermentation - Chou-Chiang Kuo; Ching-An Lin; Jing-Yi Chen; Ming-Tse Lin; Kow-Jen Duan (Biotechnology Letters, 2009)

Characteristics analysis for the flash flood-induced debris flows - Chen Chien-Yuan; Chen Lien-Kuang; Yu Fan-Chieh; Lin Sheng-Chi; Lin Yu-Ching; Lee Chou-Lung; Wang Yu-Ting; Cheung Kei-Wai (Natural Hazards, 2008)

Expression and localization of Tmie in adult rat cochlea - Mao-Chang Su; Jiann-Jou Yang; Ming-Yung Chou; Chung-Han Hsin; Ching-Chyuan Su; Shuan-Yow Li (Histochemistry and Cell Biology, 2008)

Gene expression variation increase in trisomy 21 tissues - Ching Yu Chou; Li Yu Liu; Chien Yu Chen; Cheng Hsien Tsai; Hsiao Lin Hwa; Li Yun Chang; Yi Shing Lin; Fon Jou Hsieh (Mammalian Genome, 2008)

Cell Membrane Diversity in Noncovalent Protein Transduction - Betty Revon Liu; Jyh-Ching Chou; Han-Jung Lee (The Journal of Membrane Biology, 2008)

Isolation and characterization of the zebrafish Danio rerio insulin-like growth factor binding protein-3 promoter region - Ming Jun CHOU; Jian Chyi CHEN; Jyh Yih CHEN; Hong Yi GONG; Li Tzu LI; Tzou Chi HUANG; Jen Leih WU; Ching Ming KUO (Fisheries Science, 2008)

A Bacterial Indole-3-acetyl-L-aspartic Acid Hydrolase Inhibits Mung Bean (Vigna radiata L.) Seed Germination Through Arginine-rich Intracellular Delivery - Kevin Liu; Han-Jung Lee; Sio San Leong; Chen-Lun Liu; Jyh-Ching Chou (Journal of Plant Growth Regulation, 2007)

Model-based ankle joint angle tracing by cuff electrode recordings of peroneal and tibial nerves - Chou-Ching K. Lin; Ming-Shaung Ju; Hang-Shing Cheng (Medical & Biological Engineering & Computing, 2007)

Induction And Characterization of an Indole-3-acetyl-L-alanine Hydrolase From Arthrobacter Ilicis - Jyh-Ching Chou; Yun-Bin Huang (Journal of Plant Growth Regulation, 2005)

Characterization of the genomic structures and selective expression profiles of nine class I small heat shock protein genes clustered on two chromosomes in rice (Oryza sativa L.) - Jiahn-Chou Guan; Tsung-Luo Jinn; Ching-Hui Yeh; Shi-Pin Feng; Yih-Ming Chen; Chu-Yung Lin (Plant Molecular Biology, 2004)

Winter Distribution of Diatom Assemblages in the East China Sea - Kuo-Ping Chiang; Yu-Hsuan Chou; Jeng Chang; Gwo-Ching Gong (Journal of Oceanography, 2004)

Pattern classification using tabu search to identify the spatial distribution of groundwater pumping - Ching-Pin Tung; Chun-An Chou (Hydrogeology Journal, 2004)

Cloning and Expression of the Insecticidal Crystal Protein Gene Cry 1Ca9 of Bacillus thuringiensis G10-01A from Taiwan Granaries - Suey-Sheng Kao; Feng-Chia Hsieh; Ching-Chou Tzeng; Yeong-Sheng Tsai (Current Microbiology, 2003)

Wogonin and fisetin induction of apoptosis through activation of caspase 3 cascade and alternative expression of p21 protein in hepatocellular carcinoma cells SK-HEP-1 - Yen-Chou Chen; Shing-Chuan Shen; Woan-Rouh Lee; Hui-Yi Lin; Ching-Huai Ko; Chun-Ming Shih; Ling-Ling Yang (Archives of Toxicology, 2002)

Structural Model of the Muscle Spindle - Chou-Ching K. Lin; Patrick E. Crago (Annals of Biomedical Engineering, 2002)

Neural and Mechanical Contributions to the Stretch Reflex: A Model Synthesis - Chou-Ching K. Lin; Patrick E. Crago (Annals of Biomedical Engineering, 2002)

Cloning of Two New cry Genes from Bacillus thuringiensis subsp. wuhanensis Strain - White-Shang Kuo; Jong-Huon Lin; Ching-Chou Tzeng; Shui-Shang Kao; Kin-Fu Chak (Current Microbiology, 2000)

Study of human forearm posture maintenance with a physiologically based robotic arm and spinal level neural controller - Ching-Ping Chou; Blake Hannaford (Biological Cybernetics, 1997)

The anthroform biorobotic arm: A system for the study of spinal circuits - Blake Hannaford; Jack M. Winters; Ching-Ping Chou; Pierre-Henry Marbot (Annals of Biomedical Engineering, 1995)

Dual stable point model of muscle activation and deactivation - Ching-Ping Chou; Blake Hannaford (Biological Cybernetics, 1992)